THE ROLE OF CONTROL PROCESSES IN REGULATING SELF- EFFICACY IN TASKS WITH HIGH PREDICTABILITY - Allakhverdov , M.V.; Lvova , O.V. (Արդի հոգեբանություն, 2021)
The study’s objective is to describe how cognitive control mechanisms influence performance in different tasks. We believe that popular resource models have disadvantages when explaining one’s effectiveness in a particular task. We argue that the limitations on one’s performance happen not because of limited cognitive resources but rather due to logically based restrictions. One of the restrictions is rooted in one’s need for consistency in their representations of the world and themselves. We infer that having a specific expectation about self-efficacy in a particular task dramatically influences the outcome: cognitive control mechanisms finetune one’s performance to agree with one’s expectations on the efficiency of said performance. In the study, we tested how regularities in stimuli influence one’s performance. In the experiment (23 subjects), we used the Musical Stroop test. For part of the trials, we used melodies as regularities, while in other trials, we presented fillers - random sets of notes. The results show that melodies reduce interference and have a faster response time than in the filler condition. We argue that it is due to the role of cognitive control mechanisms that maintain self-efficacy. We discuss the implication of the proposed approach.